1996
DOI: 10.1016/s0169-5150(96)01192-9
|View full text |Cite
|
Sign up to set email alerts
|

Production efficiency of Chinese agriculture: evidence from rural household survey data

Abstract: A shadow-price profit frontier model is developed to examine production efficiency of Chinese rural households in fanning operations. The model incorporates price distortions resulting from imperfect market conditions and socioeconomic and institutional constraints, but retains the advantages of stochastic frontier properties. The shadow prices are derived through a generalized profit function estimation. The shadow-price profit frontier is then estimated and an efficiency index based on the estimated profit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 19 publications
6
29
0
2
Order By: Relevance
“…The findings are also consistent with Rahman (2003) who reported profit efficiencies of between 0.059 and 0.83 among rice farmers in Bangladesh and also consistent with Ali and Flinn (1989) who reported the mean profit efficiency of 0.72, with ranges of 0.13 and 0.95 among Basimati rice farmers in Pakistan. Other comparable studies include Wang et al (1996) who reported a mean efficiency of 0.62 among farmers in China and Bozoğlu and Ceyhan (2007) who reported a mean efficiency of 0.82 among vegetable farms in Samsun province of Turkey. The distribution of groundnut producer over efficiency ranges reveals that 20% of the producers operate in efficiency range below 0.2 and only 3% operates on 0.8 and above efficiency level.…”
Section: Efficiency Rangesmentioning
confidence: 96%
See 1 more Smart Citation
“…The findings are also consistent with Rahman (2003) who reported profit efficiencies of between 0.059 and 0.83 among rice farmers in Bangladesh and also consistent with Ali and Flinn (1989) who reported the mean profit efficiency of 0.72, with ranges of 0.13 and 0.95 among Basimati rice farmers in Pakistan. Other comparable studies include Wang et al (1996) who reported a mean efficiency of 0.62 among farmers in China and Bozoğlu and Ceyhan (2007) who reported a mean efficiency of 0.82 among vegetable farms in Samsun province of Turkey. The distribution of groundnut producer over efficiency ranges reveals that 20% of the producers operate in efficiency range below 0.2 and only 3% operates on 0.8 and above efficiency level.…”
Section: Efficiency Rangesmentioning
confidence: 96%
“…In profit context a farmer can be scale inefficient, if the output level is at the level where product price is not equal to the marginal cost (Kumbhakar et al, 1989;Rahman, 2003). Studies found differences in the efficiency among farmers measured by regressing the predicted efficiency from the frontier production function on household characteristics (Bozoğlu and Ceyhan, 2007;Wang et al, 1996). The conventional production frontier function used to analyze the technical efficiency received a severe criticism in its capability to yield reliable estimates, particularly when farmers face different prices and have heterogeneous resources endowment (Ali and Flinn, 1989;Tzouvelekas et al, 2001).…”
Section: Theoretical Framework For Measuring Efficiency/inefficiency mentioning
confidence: 99%
“…It is generally believed that, education positively contributes in farming activities [93], and a bulk volume of literature concluded with growth and efficiency enhancing role of education [94][95][96][97]. However, an exception exists where education is found to have alternative role.…”
Section: Determinants Of Tfp Changesmentioning
confidence: 99%
“…As a result farms may exhibit different "best practice" production functions and operate at different optimal points. This led to the popularization and use of the more flexible profit function model to directly estimate farm-specific efficiency (Kumbhakar, 2001;Wang et al, 1996). The profit function framework combines technical, allocative and scale efficiency measures into one system and enables more efficient estimates to be obtained by simultaneous estimation of the system.…”
Section: Introductionmentioning
confidence: 99%